2021
DOI: 10.1108/ijhcqa-11-2020-0231
|View full text |Cite
|
Sign up to set email alerts
|

Overuse of small chest drains for pleural effusions: a retrospective practice review

Abstract: PurposeSmall-bore drains (≤ 16 Fr) are used in many centers to manage all pleural effusions. The goal of this study was to determine the proportion of avoidable chest drains and associated complications when a strategy of routine chest drain insertion is in place.Design/methodology/approachWe retrospectively reviewed consecutive pleural procedures performed in the Radiology Department of the McGill University Health Centre over one year (August 2015–July 2016). Drain insertion was the default drainage strategy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 22 publications
(41 reference statements)
0
2
0
Order By: Relevance
“…A practice audit showed that such a strategy led to almost half of the drains being inserted without a specific indication and with significant associated harms. 10 To address chest drain overuse, we developed a pleural drainage policy operationalized through an order set integrated into our electronic medical records (EMRs).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…A practice audit showed that such a strategy led to almost half of the drains being inserted without a specific indication and with significant associated harms. 10 To address chest drain overuse, we developed a pleural drainage policy operationalized through an order set integrated into our electronic medical records (EMRs).…”
mentioning
confidence: 99%
“…Historically, in our center, most nontrauma in-hospital pleural drainage procedures were performed in the radiology department, and the default procedure was a small drain insertion. A practice audit showed that such a strategy led to almost half of the drains being inserted without a specific indication and with significant associated harms 10. To address chest drain overuse, we developed a pleural drainage policy operationalized through an order set integrated into our electronic medical records (EMRs).…”
mentioning
confidence: 99%